GST and its effect on Corporate Governance- A Detailed Analysis - Yashika,; Rustagi, Varsha (The journal of contemporary issues in business and government, 2021)
Since independence in 1947, India has implemented many major taxation reforms; however, the Goods and Services Tax, also known as GSTimplementation on 1st of July, 2017, is considered to be the most remarkable. It was initially booked for execution in April 2010, however was deferred because of policy centered issues and clashing interests. The GST plot is planned to unite all roundabout assessments in India, including central extract charges, value-added taxes, and service taxes, into a single taxing system. Prior to this, distinct taxes or duties were assessed based on a wide range of mind-numbing concepts, including manufacturing costs, value addition and subtraction, origin, territorial issues, among others. The Indian taxation system has been subjected to countless committees, commissions, amendments etc. both before and after independence. Having delved into the complexities of various tax provisions, the GST has evolved into an umbrella tax covering most of the taxes and duties that will become a unified tax. Our study aims to enlighten readers on various issues concerning the origins and evolution of the GST regime, as well as its probable impact on corporate governance in general and Indian corporations in particular.